Evolution and sustainability analysis of global tungsten trade pattern from the perspective of industry chain - Xi, Xian; Zhong, Weiqiong; Zheng, Huiling (Frontiers in Earth Science, 2024)
Tungsten is an irreplaceable primary material and strategic resource for national economic development and modern national defense security. The endowment of tungsten ore resources in various countries is different; we should not only focus on the availability of tungsten ore itself but also the sustainability of its entire process from upstream supply to downstream industry demand. Analyzing the evolution of the supply and demand patterns of tungsten ore trade from the perspective of the industrial chain, identifying the key supply and demand subjects, and exploring the influencing factors of trade has become an important research topic. Therefore, we construct global tungsten trade networks based on the industrial chain, analyze its overall characteristics, explore critical trade supply and demand entities, and identify China’s trade position. We got some meaningful results: (1) The global tungsten trade networks have prominent power-law distribution characteristics. The trend of trade globalization is evident, but the dominance is still in the hands of a few developed countries or developing countries with developed manufacturing industries. (2) In different parts of the tungsten industry chain, the impact of resource endowment, industrial technology level, and geographical location on the country’s trade role is different. (3) China’s position in the global tungsten resource industry chain and value chain is constantly improving, but there is still a risk of high-end technology being “stuck.” This provides some suggestions for the systematic understanding of the evolution of the trade pattern of the tungsten industry chain and how countries occupy a dominant position in the game of tungsten resources.